Cultivation of Microalgae Chlorella vulgaris in Open Reactor for Bioethanol Production - Graziella Silva; Keilla Cerqueira; Jacqueline Rodrigues; Karollyna Silva; Diego Coelho; Roberto Souza (Phycology, 2023)
Microalgae have a high growth rate, high CO2 absorption capacity, and high content of chlorophyll, proteins, vitamins, mineral salts, carbohydrates, antioxidant substances, and fatty acids. In recent years, Chlorella vulgaris has been widely used as a feedstock for producing third-generation biofuels, such as bioethanol. Thus, this work aims to develop a strategy to increase the production scale of the microalgae Chlorella vulgaris grown in distilled reused water, supplemented with a modified BG-11 medium, to use biomass in the production of bioethanol. The total cultivation of 72 L presented a concentration of 0.415 g·L−1·d−1, with 61.32 g of final biomass. To improve carbohydrate extraction, the biomass was pre-treated with sulfuric acid at different concentrations (1.5% and 3% v/v). The hydrolyzed solution was supplemented with YPD (yeast extract peptone dextrose) medium and inoculated with Saccharomyces cerevisae yeast, initiating fermentation. In each sample, the Brix degree, cell concentration, reducing sugar concentration, and alcohol content were analyzed. The sample pre-treated with sulfuric acid 1.5% v/v was the one that presented the best result, with alcohol content after distillation of 68 °GL (Gay-Lussac). It appears that the cultivation of the microalgae Chlorella vulgaris in scale-up, with reused water, has high potential in the production of third-generation biofuel.